A novel electron-microscopic method for measurement of mineral content in enamel lesions. (October 2018) - Fowler, C.; Lynch, R.J.M.; Shingler, D.; Walsh, D.; Carson, C.; Neale, A.; Willson, R.J.; Brown, A.
Highlights: BSE-SEM assessed for measurement of mineral content in caries and erosive lesions Caries lesions - good correlation (R 2  = 0.98) with mineral loss data from TMR Erosive lesions - good correlation (R 2  = 0.99) with Vickers micro-hardness BSE-SEM analysis is rapid and low-cost method for mineral content in enamel lesions Abstract: Objective: To assess Scanning Electron Microscopy in Back-Scattered Emission mode (BSE-SEM) for measurement of lesion mineral content as a function of depth. Direct comparison is made with Transverse Micro-Radiography (TMR) and Surface Micro-Hardness (SMH) on carious and erosive lesions. Design: Caries lesions prepared from sound bovine enamel at 37 °C and pH 4.6 in unsaturated (7d) or part-saturated (8d, 4.1 mM Ca 2+, 8 mM Pi) lactic acid /methyl cellulose gel system, followed by TMR analysis. Erosive lesions prepared from sound bovine enamel (1% citric acid, pH3.8, room temperature) for 5, 10, 15 or 20 min at n = 10 per treatment group. SMH readings (Vickers diamond, 1.9 N, 20 s) were taken from acid-treated and reference areas of each sample. BSE-SEM performed on polished cross-sections of lesioned samples (Jeol JSM6490LV SEM; high vacuum, 10 keV beam voltage, magnification x500 with constant working distance of 10 mm). Under identical SEM conditions, polished standards i.e. MgF2, alumina, Mg, Al and Si provided a calibration plot of BSE-SEM signal vs. atomic number ( z ¯ ). Mineral content vs. depth plots were derived from the cross-sectional BSE-SEM data. Results: Cross-sectional BSE-SEM images clearly differentiate between caries and erosive lesions. Comparison of caries lesion mineral loss from BSE-SEM with TMR data showed good correlation (R 2  = 0.98). Similarly, comparison of BSE-SEM data from erosive lesions showed good correlation (R 2  = 0.99) with hardness loss data from SMH. Conclusion: BSE-SEM provides a relatively rapid and cost-effective method for the assessment of mineral content in demineralised tooth enamel and is applicable to both caries and erosive lesions.